Alterations in epithelial cadherin and fxyd5/dysadherin expression in colorectal cancer progression and metastasis - Lleyda, Micaela (2022)
Colorectal cancer (CRC) is the most common malignant diseaseof the digestive tract, and 2nd in incidence/mortality worldwide andin Argentina. Epithelial Cadherin (Ecad) loss has been related tocell adhesion loss, migration and invasiveness. FXYD5/Dysadherin(FXYD5) was found associated with tumor aggressiveness/metastasis in solid tumors and is a negative Ecad modulator. Studieswere initiated to characterize Ecad and FXYD5 expression inCRC and their role in tumor progression/metastasis. Transcriptexpression analysis was done in datasets from colon adenomaand CRC patient’s and cell lines (GEO; TCGA). Paired adenomas/normal tissue analysis (GSE8671; n=32) revealed decreasedECad (NT=20,884±3,342; A=16,855±2,082) and increased FXYD5(NT=1,107±435; A=3,577±1,193) (p<0.0001) in adenomas. In linewith these findings, lower Ecad and higher FXYD5 was foundin early tumors when comparing to normal tissues (GSE32323;16 pairs, Ecad NT=13.21±0.19 T=12.86±0.32, p<0.005; FXYD5NT=7.65±0.47 T=8.72±0.43, p<0.005). Similar results were obtainedin other CRC datasets (GSE4107; NT n=10 T n=12; Ecadp<0.05, FXYD5 p<0.05; GSE9348; NT n=12 T n=70; Ecad p<0.05,FXYD5 p<0.001). No differences in Ecad and FXYD5 expressionwere observed with patient gender (female n=30, male n=40; Ecadp=0.9448, FXYD5 p=0.6735) or age (50-69y (n=43), 70-93y (n=27)Ecad=0.1482; FXYD5=0.3671). When comparing MSS (n=13) andMSI (n=77) tumors (GSE24550), MSI showed higher (p<0.0001)FXYD5 and similar (p=0.1084 Ecad levels). Overall survival (TCGA)was lower (p=0.0064) in patients with high (5.153 y; n=246) thanlow (8.334 y; n=351) FXYD5. Moreover, liver metastasis (n=283;GSE159216) also showed higher FXYD5 levels (p<0.0001) thantumors (n=105; GSE178120), while Ecad levels were comparable(p=0.24). Ecad and FXYD5 expression was confirmed in HT29(High Ecad, Low FXYD5) and HCT116 (Low Ecad, High FXYD5)and are currently under study to assess the underlying mechanismsof CRC progression/aggressiveness.